Extracellular carbohydrate metabolites from Streptomyces coelicolor A3(2) - Pospísil, Stanislav; Sedmera, Petr; Halada, Petr; Petrícek, Miroslav (Journal of natural products, 2007)
A new ribose trisaccharide, alpha-Ribf-(1-->2)-alpha-Ribf-(1-->3)-alpha-Ribf (1), was isolated together with 5-O-(alpha-mannosyl)-myo-inositol (2), 2-O-(alpha-mannosyl)-myo-inositol (3), trehalose (4), and d-ribulose (5) from a submerged cultivation of Streptomyces coelicolor A3(2). The structures of these compounds were elucidated by spectroscopic and chemical methods. Concentrations of these compounds in the medium were in the range from 0.04 (1) to 0.5 (4) mg/mL.
Keywords: molekulární struktura; sacharidy; Trisaccharides; nukleární magnetická rezonance biomolekulární; Molecular Structure; Streptomyces; trisacharidy; Nuclear Magnetic Resonance, Biomolecular; Carbohydrates